PENGEMBANGAN MEDIA PEMBELAJARAN ELECRONIC BOOK (E-BOOK) BERBASIS EDMODO KELAS X SMK KARTIKATAMA METRO - Duwi Novitasari; Triani Ratnawuri; Meyta Pritandhari (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Learning Media is one of the most important components of education for teachers and students in the learning process. So we need learning media that can be used and studied at any time for all students but also follows the development of technology. Based on these problems the learning media in the form of books used by students namely Edmodo-based E-books can be used for alternative solutions to existing problems. The aim of this development is to produce a valid and practical e-book.The Development Model used by the ADDIE model consists of 5 stages (Analysis, Design, Development, Implementation, and Evaluation). The results showed that edmodo-based e-books are valid for use in the learning process. The results of validation by media experts with 88% criteria are very valid, material experts with 86% criteria are very valid. The results of edmodo-based e-book products testing to students with a percentage of 86% criteria are very practical, this shows that the e-book can already be used as a medium of accounting learning. Based on the recapitulation, it can be concluded that e-book based on Edmodo is a valid and practical learning media in the learning process. Keywords: E-Book, Edmodo, Learning Media